2021
DOI: 10.1177/1356336x211027072
|View full text |Cite
|
Sign up to set email alerts
|

‘Same, same, but different?!’ Investigating diversity issues in the current Austrian National Curriculum for Physical Education

Abstract: Discussions on educational policy are shaped by current societal transformations associated with diversity. At the same time, the most recent reform of the Austrian National Curriculum for Physical Education (NCPE) was driven by the desire to stipulate standardised learning outcomes. Building upon Bernstein's framework, this paper explores to what extent issues of diversity are addressed in curricular documents, which inform and structure teaching and learning processes. Based on a qualitative content analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Several studies from the perspective of PE teachers revealed tensions between the educative and physical dimensions of PE in Finland (Mihajlovic, 2019) and Australia (Pill & Stolz, 2015), which often stem from personal sport experiences from out-of-school settings. In line with these findings, recent studies from England and Austria confirm the PE teachers' dilemma between a more traditional view of sports and the educative dimensions of PE in the curricular approaches (Herold, 2020;Meier et al, 2021).…”
Section: The Rel Ationship Bet Ween Physical Education Sport and Soci...supporting
confidence: 57%
See 4 more Smart Citations
“…Several studies from the perspective of PE teachers revealed tensions between the educative and physical dimensions of PE in Finland (Mihajlovic, 2019) and Australia (Pill & Stolz, 2015), which often stem from personal sport experiences from out-of-school settings. In line with these findings, recent studies from England and Austria confirm the PE teachers' dilemma between a more traditional view of sports and the educative dimensions of PE in the curricular approaches (Herold, 2020;Meier et al, 2021).…”
Section: The Rel Ationship Bet Ween Physical Education Sport and Soci...supporting
confidence: 57%
“…As previous research has revealed, only a so‐called narrow understanding of bodies—idealized through heterosexuality, binary gender and certain body ideals—are recognized as normal and healthy in PE (Giese & Ruin, 2018; Webb et al, 2008). Ambivalent positions regarding the educative dimensions of PE and the traditional view of sports can be found in the Finnish national curriculum (Kujala & Hakala, 2015) and other international curricular approaches (Giese & Ruin, 2018; Meier et al, 2021). The physical dimensions of PE are often related to a more traditional understanding of the aims of PE and student assessment which are not supportive when addressing student diversity in PE.…”
Section: The Relationship Between Physical Education Sport and Social...mentioning
confidence: 99%
See 3 more Smart Citations